Bhāra Book: An Interactive Learning Medium to Support Self-Help Skills in Children with Intellectual Disabilities - Agung Taufik; Nuansa Kamil; Rayhan Octavian Pratama Sakti; Kaley Elhaq; Dhimas Wicaksono Nurrahman; Barra Raziq Diviarsa (GLOBAL SCIENTS PUBLISHER, 2026)
Children with intellectual disabilities require specialized educational support to develop self-help skills, basic academic abilities, and emotional regulation. However, the availability of interactive learning media that integrate these developmental aspects remains limited. This study aimed to develop Bhāra Book as an interactive learning medium designed to support self-help skills, pre-literacy, pre-numeracy, and emotional recognition for children with intellectual disabilities. This research employed a qualitative approach, with data collected through direct observation and in-depth interviews involving teachers and parents at several special schools (SLB) in Cianjur Regency. The findings indicate that Bhāra Book provides practical support for daily self-care training, basic academic learning, and emotional reflection. Observations showed positive engagement from children with mild intellectual disabilities, while feedback from teachers and parents highlighted the usefulness, simplicity, and visual appeal of the media. The results suggest that Bhāra Book contributes to diversifying learning media and supports the rights and opportunities of children with intellectual disabilities to optimize their development.